Genetic variations in the DYNC2H1 gene causing SRTD3 (short-rib thoracic dysplasia 3 with or without polydactyly) - Chen, Wenqi; Li, Yazhou; Zhang, Jing; Yuan, Yufan; Sun, Donglan; Yuan, Jiayu; Yang, Kai; Liang, Ying; Guo, Qing (Frontiers in Genetics, 2023)
Background and aims: Short-rib thoracic dysplasia 3 with or without polydactyly (SRTD3) represents a type of severe fetal skeletal dysplasia (SD) characterized by shortened limbs, narrow thorax with or without polydactyly, which is caused by the homozygous or compound heterozygous mutations in the DYNC2H1 gene. SRTD3 is a recessive disorder, identification of the responsible genetic variation would be beneficial to an accurate prenatal diagnosis and well-grounded counseling for the affected families. Materials and methods: Two families having experienced recurrent fetal SDs were recruited and submitted to a multiplatform genetic investigation. Whole-exome sequencing (WES) was performed with samples collected from the probands. Sanger sequencing and fluorescent quantitative PCR (qPCR) were conducted as validation assays for suspected variations. Results: WES identified two compound heterozygous variations in the DYNC2H1(NM_001080463.2) gene, namely c.2386C>T(p.Arg796Trp) and c.7289T>C(p.Ile2430Thr) for one; and exon(64-83)del and c.8190G>T(p.Leu2730Phe) for the other, respectively. One variant in them, exon(64-83)del, was novelly identified. Conclusion: The study detected two compound heterozygous variation in DYNC2H1 including one novel deletion: exon(64-83)del. Our findings clarified the cause of fetal skeletal dysplasia in the subject families, provided guidance for their future pregnancies, and highlighted the value of WES in diagnosis of skeletal dysplasia with unclear prenatal indications.